Pendidikan kesehatan melalui seminar dan diskusi sebagai alternative penanggulangan perilaku merokok pada remaja pelajar SLTA di Kodya Yogyakarta = Health education through seminar and discussion as analternative for ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Reports from World Health Organization (WHO) indicated that the number of smokers in developing countries has increased in the past ten years. Indonesia ranks fifth among countries with the largest number of smokers. This condition needs serious consideration because of the hazard of smoking. Information about the danger of smoking are much less available than the number of cigarette advertisements. Thus, health education is very much needed. The objective of this study is to find out the effectiveness of health education through seminars and disscussions for senior high school students in the Yogyakarta municipality. This study is also intended to identify factors which influence smoking behavior. Two hundred and forty three male senior high school students from 12 senior high schools in Yogyakarta municipality were screened on surveys in 15 senior high schools and participated in this study. Twelve senior high schools were chosen based on the high number of smokers. The subjects of this study divided into three groups. Seminar groups consisted of 98 students from three senior high schools, discussion groups were 30 students from three senior high schools and 115 students from six senior high schools were the groups which only receive the health education material without teacher or facilitator assistance (non-assistance groups). Those groups were divided randomly. The Counseling and Guidance Teachers conducted the health education. They were trained twice and the health education was also provided twice. Results showed that health education through seminars and discussions are only effective for increasing knowledge about the risks of smoking and decreasing positive attitude toward smoking. The positive beliefs regarding smoking were not changed, while the number of cigarettes smoked by non-assistance groups declined. Health education through seminars was more effective than health education through discussion.